До питання про договір рахунку умовного зберігання (ескроу) - Іванова, К. Ю. (НДІ ПЗІР НАПрНУ, 2019)
Робота присвячена аналізу нової для українського законодавства конструкції – договору рахунку умовного зберігання (ескроу). Наводиться механізм регламентації відносин сторін за допомогою цього договору та ви-являються особливості його української моделі. // The scientific work is dedicated to exploring the escrow agreement that is a new legal construction to Ukrainian legislation. The mechanism for regulating the relations of the parties to the agreement (counterparties) with the help of this agreement is given; the peculiarities of the Ukrainian model of this agreement are revealed.
Keywords: ескроу; договір рахунку умовного зберігання; банківський рахунок; ескроу-агент; escrow; escrow agreement; bank account; escrow agent